ADAT NATIONAL PARK AS LEGAL POLITICS OF LIVING SPACE OF ANAK DALAM TRIBE - Erwin, Muhamad; Yusriyadi, Yusriyadi (Diponegoro Law Review, 2024)
The Anak Dalam Tribe in Bukit Dua Belas National Park faces significant challenges due to conflicting paradigms between state control over national parks and customary land rights which sacrifice the interest of Anak Dalam Tribe. This study underscores the urgent need for a shift in the conservation legal paradigm to safeguard the tribe's living space. Employing a non-doctrinal research method, it examines law as a social reality within the tribe's habitat. The findings advocate for a new conservation model termed "Adat National Park." This model integrates traditional, environmentally friendly practices in collaboration with the National Park Authority. Such an approach aims to harmonize state conservation efforts with indigenous land rights, ensuring the tribe's active participation in management and the preservation of their cultural and ecological heritage. By adopting this model, it is possible to create a balanced and sustainable conservation strategy that respects both state interests and the rights as well as traditions of the Anak Dalam Tribe.